(3GdehLR aj GdWHs - (3GdbQTj, GHf GdfajS, YdGA GdOjf, Ydj Hf CHj GdMRe, J(B687 (3g`s ((3GdaJM Hf YHO Gddg Hf GdaJM GdHfOGQjs)
(3ChdgG (B:s
(3HSe Gddg bGd GdTjN GdGeGe bO QJHJ gPG GdcJGH Ydi CQHYI afhf Gdaf GdChd aj bhGYO LRFj GdWH CYfj YdejI hYedjI Hbhd cdj ; Gdaf GdKGfj aj GdCOhjI hGdCZPjI s
(3BNQgG (B:s
(3hcHO GdcdH GdcdH JTaj deYVhVI ajDef ef GdaRY ef GdeGA hbO TgO HPdc LeGYI hbO YVJ cdHI cdH CQHYjf QLdG aCcd HYVge ef cHOI hGSJfca GdHGbj ef CcdgG aef CcdgG de jeJ hef gGgfG jNJge GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\270s
(3cTa GdXfhf (B2\1899s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs